2021
DOI: 10.1038/s41598-021-92391-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeted SPION siderophore conjugate loaded with doxorubicin as a theranostic agent for imaging and treatment of colon carcinoma

Abstract: Recently, the siderophores have opened new horizons in nanomedicine. The current study aimed to design a theranostic platform based on superparamagnetic iron oxide nanoparticles-pyoverdine (SPION/PVD) conjugates bound to MUC1 aptamer (MUC1Apt) and loaded with doxorubicin (DOX) as an anti-cancer agent. The SPION/PVD complex was covalently conjugated to MUC1Apt and loaded with DOX to prepare a targeted drug delivery system (SPION/PVD/MUC1Apt/DOX). The investigation of cellular cytotoxicity and uptake of formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…The investigators showed that the PVD-SPION-MUC1 Apt complex was successfully taken up by cancer cells, and conferred tumor inhibitory growth effects and improved survival in mice bearing C26 colon carcinoma (221). This complex also served as a diagnostic agent that improved contrast at the tumor site in magnetic resonance images (221). This study is one of the first to show the potential of siderophores as chemotherapy delivery agents and diagnostic tools in cancer.…”
Section: Siderophores As Mediators Of Drug Deliverymentioning
confidence: 80%
See 2 more Smart Citations
“…The investigators showed that the PVD-SPION-MUC1 Apt complex was successfully taken up by cancer cells, and conferred tumor inhibitory growth effects and improved survival in mice bearing C26 colon carcinoma (221). This complex also served as a diagnostic agent that improved contrast at the tumor site in magnetic resonance images (221). This study is one of the first to show the potential of siderophores as chemotherapy delivery agents and diagnostic tools in cancer.…”
Section: Siderophores As Mediators Of Drug Deliverymentioning
confidence: 80%
“…A recent study conjugated the siderophore PVD from P. aeruginosa, a mixed-type siderophore with hydroxamate and catecholate groups, to synthesize superparamagnetic iron oxide nanoparticles (SPION) (221). The PVD-iron complex has strong binding and high stability, which protects it from hydrolysis and enzymatic degradation.…”
Section: Siderophores As Mediators Of Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, theranostic agents, including MRI contrast agents, have been developed for the purpose of diagnosis and therapy at the same time [37]. For example, a tumor specific magnetic nanoparticle-loaded doxorubicin agent has been developed by various research groups in the imaging and treatment of cancer [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Nosrati et al . used AS1411 targeted SPIONs and loaded the aptamer with DOX for MRI and therapy of colon carcinoma 172 . While in vivo MRI in C26 xenografts could not clearly separate AS1411 and scrambled ssDNA conjugated SPIONs, the targeted formulation showed a significantly better tumor growth inhibition.…”
Section: Aptamers For Theranostic Applicationsmentioning
confidence: 99%